INFLUENCE PROFITABILITY AND LIQUIDITY ON SHARE RETURN AT PT INDOFOOD SUKSES MAKMUR Tbk WHICH ARE LISTED ON THE INDONESIA STOCK EXCHANGE - Durrah Safira; Ifvac Vara Azzerah; Riska Munanda; Nur Azizah; Qhisthina Atikah (RADJA PUBLIKA, 2023)
This descriptive qualitative research aims to examine the effect of profitability and liquidity on stock returns at PT Indofood Sukses Makmur Tbk which is listed on the Indonesia Stock Exchange (IDX) in the 2019-2023 period. The variables studied include liquidity, profitability, and stock returns. This study uses a qualitative approach by collecting and analyzing secondary data, including company financial statements and other public information. The analysis was carried out by describing and interpreting the data obtained. The results of this study are expected to provide a deeper understanding of the relationship between liquidity, profitability and stock returns at PT Indofood Sukses Makmur Tbk. These findings will be useful to investors, financial analysts, and enterprise management in making smarter investment decisions. In addition, this research can also contribute to the development of knowledge in the field of financial analysis and corporate financial management. Thus, this research is expected to provide new insights and better understanding regarding the factors that influence stock returns in companies listed on the IDX.